The evolution of rural society in western Peloponnese: Metochi (Achaia) - Sivignon, Michel (The Greek Review of Social Research, 1981)
Metochi is a commune in the littoral plain of western Peloponnese. It is composed of two main hamlets: Metochi and Lappa. Metochi is the eldest and formally most important settlement. It is now declining whereas Lappa is faringbetter thanks to the higher quality ofits soils, its location on the main linesof communication and above all thanks to its irrigation capacities. The average surface of its farms is twice as big as in Lappa and water is plentiful: the community is now compos ed of a thriving village. Lappa, and a poor village, Metochi, whose in habitants have to work for Lappa’s farmers to make up their living resources.